Investigation of the Impact Resistance Behavior of Customized Hair Clipper Comb Fabricated by Fused Deposition Modeling - Ali, Uzair; Saeed, Hasan Aftab; Ahmed, Bilal Anjum; Butt, Sajid Ullah; Khan, Rehan (Sustainability, 2022)
This study consists of the development of a hair clipper comb finite element (FE) model, impact test analysis on the FE model, fabrication of the product using commercially available materials, followed by physical impact testing of the comb. Moreover, microscopic examination of the combs was performed to analyze the quality of the product and correlate the defects with the failure mechanism. The 3D model of comb for a Philips hair clipper was developed using ONSHAPE software, followed by a design study to understand the impact resistance of the product. The design study was performed using finite element analysis (FEA) explicit dynamic module, where two hair clipper comb designs, one with a solid body and the other with a shell were subjected to drop test simulation in two orientations: leg and head drop. Two readily available 3D printable plastic materials, Acrylonitrile Butadiene Styrene (ABS) and Polylactic acid (PLA) were selected for the FEA simulation while the comb was subjected to free fall from a height of 5 ft (1.67 m). The comb was dropped in two orientations: the head drop configuration and the leg drop configuration. For all combinations, the maximum stresses generated as a result of impact were noted and experiments performed to validate the simulation results. The four models were fabricated using fused deposition modeling (FDM) technique and were manually dropped from the same height. In line with the simulated results, models prepared from PLA material failed upon the impact while ABS samples having a comparatively better impact resistance sustained the impact without failure. Finally, fracture surface morphologies of the failed PLA component and the surface of ABS in as-printed condition were analyzed using Scanning Electron Microscopy (SEM). Based on the obtained results, the shell model made of ABS material turns out to be the most suitable choice out of all the designs considered.